2022
DOI: 10.1038/s41598-022-05325-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 reinfections among naturally infected and vaccinated individuals

Abstract: The protection against emerging SARS-CoV-2 variants by pre-existing antibodies elicited due to the current vaccination or natural infection is a global concern. We aimed to investigate the rate of SARS-CoV-2 infection and its clinical features among infection-naïve, infected, vaccinated, and post-infection-vaccinated individuals. A cohort was designed among icddr,b staff registered for COVID-19 testing by real-time reverse transcriptase-polymerase chain reaction (rRT-PCR). Reinfection cases were confirmed by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 62 publications
5
93
0
10
Order By: Relevance
“…13 Recent studies have demonstrated that Omicron-infected cases tended to cause mild symptoms such as pharyngitis, headache, nasal [29] which corroborates with our data. Despite the fact that three subjects have a booster, with the third/additional dose, they developed symptomatic COVID-19, as others with complete vaccination and previous history of COVID-19 [7]. These data support the findings that neither the current vaccines available nor previous history of COVID-19 are sufficient to establish a robust response toward the Omicron variant and to promote a reduced risk of infection.…”
Section: Tracking Reinfection Cases In Rio Grande Do Norte Brazilsupporting
confidence: 64%
See 1 more Smart Citation
“…13 Recent studies have demonstrated that Omicron-infected cases tended to cause mild symptoms such as pharyngitis, headache, nasal [29] which corroborates with our data. Despite the fact that three subjects have a booster, with the third/additional dose, they developed symptomatic COVID-19, as others with complete vaccination and previous history of COVID-19 [7]. These data support the findings that neither the current vaccines available nor previous history of COVID-19 are sufficient to establish a robust response toward the Omicron variant and to promote a reduced risk of infection.…”
Section: Tracking Reinfection Cases In Rio Grande Do Norte Brazilsupporting
confidence: 64%
“…The dissemination of these variants, so-called variants of concern (VoC), are also closely associated with higher viral load [3], and/or rates of reinfection [4] among individuals. By the fact that VoCs can surpass the protective effects of humoral immunity induced either by natural infection or by vaccination [5,6], this poses an additional challenge to curb the pandemic since the highest number of new cases and an increased number of reinfections still have been reported worldwide in 2022 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect of this pandemic regards both reinfections and infections among vaccinated subjects. While, on the one hand, the pandemic growth curve has been significantly reduced, on the other hand, in various health contexts worldwide, cases of reinfection have been detected in subjects previously positive for SARS-CoV-2, along with cases of infection diagnosed in vaccinated subjects (conventionally called "vaccine breakthroug") [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that IgG concentrations in the serum and lung of patients treated with IgG prevents pulmonary infection, but that IgG diffusion into mucosal membranes of the upper airways is insufficient to prevent sinus infection. Thus, the complementarity between a strong systemic response mediated by IgG in the lung and a mucosal response at infection sites mediated by IgA could explain why a better protection has been observed in individuals who were vaccinated after a previous SARS-CoV-2 infection 86 . Delivered intramuscularly, available SARS-CoV-2 vaccines prevent the development of COVID-19 once the pathogen has crossed mucosal barriers, and mostly result in the systemic production of antibodies and recruitment of T lymphocytes in the lower respiratory tract, but not in the upper respiratory tract.…”
Section: Delivery Routes For Sars-cov-2 Vaccines—an Opportunity For M...mentioning
confidence: 99%